2015
DOI: 10.13075/ijomeh.1896.00332
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between occupational functioning and stress among radio journalists – Assessment by means of the psychosocial risk scale

Abstract: Well-known relationships between stress level, satisfaction and occupational functioning were confirmed. The most important conclusion refers to the fact that psychosocial risks and stress analysis should be based on the understanding of specificity of each occupation or even position. It is so, because the same job characteristic may pose a challenge for one person, while for another--it can result in extreme discomfort and anxiety--such an attitude broadens understanding of the phenomenon. We also confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Inter-correlations between JATS dimensions (9)(10)(11)(12)(13)(14) are ranging from r = .179 to r = .555, with 7 out of 15 being <.400 (Table 2). There is no multicollinearity problem between the predictors (1)(2)(3)(4)(5)(6)(7)(8), or between predictors and dependent variables (JATS dimensions).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-correlations between JATS dimensions (9)(10)(11)(12)(13)(14) are ranging from r = .179 to r = .555, with 7 out of 15 being <.400 (Table 2). There is no multicollinearity problem between the predictors (1)(2)(3)(4)(5)(6)(7)(8), or between predictors and dependent variables (JATS dimensions).…”
Section: Resultsmentioning
confidence: 99%
“…O = Overall significance in group differences in ANOVA Table 2 Spearman correlations of all study variables (Spearman correlations). Cronbachs alphas of the interval scaled measures (6)(7)(8)(9)(10)(11)(12)(13)(14)…”
Section: Resultsmentioning
confidence: 99%
“…Through the app, employees will answer the minipsychosocial stressors at work scale (Mini-PSWS), a reduced version of the psychosocial stressors at work scale. 46 This screening tool contains 16 items and it is conceptually grounded in the typology of workplace stressors developed by the European Framework for Psychosocial Risks Management PRIMA-EF 47 and supported by a large body of research which showed direct relationships between workplace stress and burnout, depression, anxiety, adjustment disorders, somatization, chronic fatigue, psychotropic drugs consumption and many others conditions. 48,49 Employees will receive through the app a detailed and tailored report with recommendations based on their responses to the Mini-PSWS.…”
Section: Interventionmentioning
confidence: 99%